GAMBARAN KEMANFAATAN LAYANAN KESEHATAN DASAR MENJANGKAU MASYARAKAT DI KEPULAUAN DENGAN PROGRAM PERAHU SEHAT PULAU BAHAGIA (PSPB): Studi Kasus Puskesmas Sabutung Kecamatan Liukang Tuppabiring Utara - Rusdi; Rosdiana; Irman Idrus (JSSHA ADPERTISI JOURNAL, 2021)
The Public Health Center in 2014 explained that the puskesmas is a First Level health service facility that organizes Public Health Efforts (UKM) and Individual Health Efforts (UKP), especially for promotion and prevention efforts (Tasim, 2020). The Sabutung Health Center outlined the Minister of Health Regulation No.75 of 2014 by launching the Happy Island Healthy Boat (PSPB) service (Kompak, 2020). PSPB service is an initiative introduced by Puskesmas Sabutung to implement puskesmas services outside island- based buildings (Kompak, 2020). The research was conducted on Sabutung Island. In particular Puskesmas Sabutung, Liukang Tuppabiring Utara Regency, from July to December 2020. The type of research used is a quantitative research using a cross- sectional approach, namely the object of research to be measured and observed and carried out simultaneously using dependent and independent variables (Sugyono, 2017). The results of this study showed that the community with the awareness that the use of PSB health services was bad was only 2 (3.33%), while the community (respondents) who had awareness of the benefits of PSB services in supporting health services at the Sabutung Health Center stated that it was good, namely 58 (96.7%).